2009
DOI: 10.1158/0008-5472.can-09-1627
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Cytokines and Tumor Cell Biology Determine Spontaneous Breast Cancer–Specific Immune Responses and Their Correlation to Prognosis

Abstract: Spontaneous immune responses in cancer patients have been described. Yet their clinical relevance and the conditions for their generation remain unclear. We characterized conditions that determine immune responses in primary breast cancer patients. We used tetramer analysis, ex vivo IFN-γ ELISPOT, cytotoxicity assays, and ELISA in 207 untreated patients and 12 Her-2/neu-specific CD8 T-cell lines to evaluate tumorspecific T cells (TC) in the bone marrow or MUC1-specific antibodies in the blood. Multiplex analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…In this context, we showed that cytokines such as TGF-b and TNF-a detected in ovarian tumor derived-supernatants, were involved in this pDC dysfunction. The inhibitory role of TGF-b is consistent with a previous study showing that increased intratumoral IFN-a levels correlates with reduced TGF-b1 in breast cancer patients (33). Moreover, recent reports in mice and human showed that this cytokine contributes to peyer patches, splenic stromal, and tumor environments mediated inhibition of pDC capacity to produce IFN-a (29,34,35).…”
Section: Discussionsupporting
confidence: 90%
“…In this context, we showed that cytokines such as TGF-b and TNF-a detected in ovarian tumor derived-supernatants, were involved in this pDC dysfunction. The inhibitory role of TGF-b is consistent with a previous study showing that increased intratumoral IFN-a levels correlates with reduced TGF-b1 in breast cancer patients (33). Moreover, recent reports in mice and human showed that this cytokine contributes to peyer patches, splenic stromal, and tumor environments mediated inhibition of pDC capacity to produce IFN-a (29,34,35).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that in some CRCs dominant regulatory mechanisms are active, either directing TC responses into other functional polarization, which renders them anergic or exhausted, or inhibiting their functional activity. We indeed found higher concentrations of TNF-α particularly in those tumors that contained lower levels of the TC-suppressive Treg effector cytokine, TGF-β1 (34). Thus, increased intratumoral TNF-α concentrations indicate not only systemic induction of functionally potent CTL responses but also their dominance in situ over a major local immune-suppressive mechanism.…”
Section: Discussionmentioning
confidence: 61%
“…CD4 + and CD8 + TILs from CRCs that rested overnight without stimulation showed no expression of TNF-α, while subsequent polyclonal activation with anti-CD3/anti-CD28 antibodies caused marked TNF-α expression in CD8 + and CD4 + TILs ( Figure 1, A and B) and also in freshly isolated blood-derived TCs from 5 patients with CRC ( Figure 1C). Altogether, activation-induced TNF-α expression was lower in TILs than in peripheral bloodderived TCs (PBTCs) from the patients -most likely reflecting the exhausted state of intratumoral TCs (34). Taken together, TNF-α expression in TILs is restricted to a population of activated TCs.…”
Section: Tnf-α Expression Is Restricted To Activated Tumor-infiltratimentioning
confidence: 96%
See 1 more Smart Citation
“…However, we need to define new prognostic tools and develop highly targeted therapies (Emens et al, 2004). Immune functions and their relation to prognosis in cancer patients is an area of great interest for many researchers in recent years (Domschke et al, 2009). A study revealed that the preoperative expression levels of cluster of differentiation (CD) of the CD3+, CD4+/CD8+ and NK+ cells in patients with colorectal cancer was positively correlated with prognosis (Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%